2019
DOI: 10.1186/s40779-019-0228-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex-based differences in the prevalence of acute mountain sickness: a meta-analysis

Abstract: BackgroundWhen lowlanders rapidly ascend to altitudes > 2500 m, they may develop acute mountain sickness (AMS). The individual susceptibility, ascending velocity, time spent at altitude, activity levels and altitude reached are considered risk factors for AMS. However, it is not clear whether sex is a risk factor. The results have been inconclusive. We conducted a meta-analysis to test whether there were sex-based differences in the prevalence of AMS using Lake Louise Scoring System.MethodsSystematic searches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 44 publications
4
25
0
1
Order By: Relevance
“…Sex differences in AMS has been previously report, but with inconsistent conclusions. A meta-analysis supported higher susceptibility in women [24]. In the current study, we confirmed higher rate of AMS in women.…”
Section: Sex Differencessupporting
confidence: 86%
“…Sex differences in AMS has been previously report, but with inconsistent conclusions. A meta-analysis supported higher susceptibility in women [24]. In the current study, we confirmed higher rate of AMS in women.…”
Section: Sex Differencessupporting
confidence: 86%
“…However, according to [ 116 ], susceptibility to AMS does not differ according to gender. The authors of [ 117 , 118 ] found that women are more likely to develop AMS, but at the same time there are data demonstrating that, vice versa, men are more predisposed to suffer from AMS than women [ 119 ]. Thus, this question remains not fully understood and requires further research paying attention to the reproductive status and female estrous cycle phase.…”
Section: Physiological Biochemical and Molecular-biological Charmentioning
confidence: 99%
“…As a result, only 16.9% of registered studies involved children. As a factor of disease outcomes ( Hou et al, 2019 ), only 2.5% studies focus on the participants’ gender. The included clinical studies involved disease prevention, diagnostic accuracy, drug treatment, medical devices, prognosis, as well as treatment of critical COVID-19.…”
Section: Discussionmentioning
confidence: 99%